Reconstruction of Municipal Streets - Aguilar Dondi, Alvaro (2025)
Detailed Description of the Analysis, Decision-Making, Budgeting, and Construction Phases for the Reconstruction of Los Cerros Street in Escazú. Los Cerros Street serves as an access road to a residential area located in the southwest sector of the Escazú Canton. Faced with the deteriorated condition of the road, the local residents took the initiative to pursue a long-term reconstruction solution. Through community organization and collaboration, they assumed responsibility for the project and made well-informed decisions to ensure its successful execution.